Child friendship patterns at a refugee center in Greece - Palaiologou, Nektaria; Prekate, Viktoria (Frontiers in Education, 2023)
Schools provide opportunities to young refugee communities for initiating connections and maintaining friendships with local native peers. However, segregated accommodation structures, such as large, remote Refugee Hospitality Centers, can hinder this process. A small-scale study was conducted at Skaramagas refugee camp in the outskirts of Athens, to investigate the number and type of friendships formed by adolescent refugees, including friendships with refugees/migrants from other countries, as well as native peers. Certain sociological factors, such as age, sex, country of origin, school attendance and duration of stay in Greece, were examined. The study was conducted through semi-constructed interviews with 21 adolescent students at the Refugee Hospitality Center, all of whom attended onsite non-formal language classes, although only half attended formal education outside the camp. The results indicate the positive impact of school attendance on relational inclusion and widening friendship circles. Children attending local formal schools were more likely to widen their friendship circles and form friendships with native peers than children who only attended non-formal classes inside the camp. Girls appear to have fewer friendships than boys, ethnicity and age do not seem to provide any significant differentiation, whereas duration of stay in Greece does not seem to affect socialization patterns directly. This study examines the patterns of friendship formation among newly arrived refugee adolescents and highlights the impact of schooling on relational inclusion, even at highly segregated accommodation structures, such as remote refugee camps.